PENERAPAN PEMBEAJARAN KOOPERATIF TIPE STUDENT ACTIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI PERUBAHAN MAKHLUK HIDUP SISWA KELAS III SD NEGERI 1 LANDUNGSARI KABUPATEN MALANG - Chamroh, Yakut Tatil; Anwar, Moh. Farid Nurul; Chotimah, Chusnul (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2025)
This study aims to improve the learning outcomes of third-grade students at SD Negeri 1 Landungsari on the topic of changes in living beings by implementing the cooperative learning model Student Active Learning (SAL). The method used is Classroom Action Research (CAR), conducted in two cycles, which include planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observations, and interviews, and were analyzed using descriptive quantitative methods. In the pre-cycle stage, the class average score was still at 65.00 with a low mastery level of 14.71%. The results showed a significant improvement in student learning outcomes after implementing the SAL model. The average score increased from 69.70 in the first cycle to 84.42 in the second cycle, with mastery learning rising from 29.42% to 76.47%. Furthermore, applying the SAL model enhanced students’ active participation in learning, particularly in group discussions and presentations. In conclusion, the SAL learning model improved learning outcomes and students’ critical thinking, communication, and collaboration skills. Therefore, this model can be considered a relevant strategy for implementing the Merdeka Curriculum to enhance elementary school learning quality.